Rxsports carnival 2025: Dominating the moment, celebrating the legacy - Mahfuz, Puteri Nurul Nuha; Azmi, Nur Aina; Othman, Ahmad Azani; Surindar Singh, Gurmeet Kaur (Faculty of Pharmacy, 2026)
The Society of Pharmacy Students (SOPHYS), Sekretariat Mahasiswa Fakulti (SMF) and Majlis Perwakilan Pelajar (MPP) 2024/2025, Faculty of Pharmacy, Universiti Teknologi MARA (UiTM) Puncak Alam successfully organised RxSports Carnival 2025 from 12 to 14 December 2025, in conjunction with the Faculty of Pharmacy’s 25th anniversary celebration. Carrying the theme “Dominate the Moment, Celebrate the Legacy”, the annual event provided a lively platform to strengthen relationships among students, staff, and alumni while promoting a healthy and competitive lifestyle.